Investigations on metallization in FDM build ABS part using electroless deposition method. (August 2015) - Equbal, Azhar; Sood, Anoop Kumar
Highlights: Electroless copper deposition on ABS parts were studied through two different routes. For validation of results four different acidic baths are used. Comparisons are made on the basis of electrical performance and surface morphology. For the 1st time the result through conventional electroless method is expressed in values. Abstract: Electroless metallization of ABS parts has been studied on flat part surface. These parts are fabricated on fused deposition modelling machine using ABS (acrylonitrile–butadiene–styrene) as part material. Copper deposition on ABS parts using two different surface conditioning processes namely ABS parts prepared using chromic acid for etching and ABS parts prepared using solution mixture of sulphuric acid and hydrogen peroxide (H2 SO4 /H2 O2 ) for etching has been performed. After surface preparation using these routes, Cu (copper) is deposited by electroless method using four different acidic baths. The acidic baths used are 5 wt% CuSO4 (copper sulphate) with 15 wt% of individual HF (hydrofluoric acid), H2 SO4 (sulphuric acid), H3 PO4 (phosphoric acid) and CH3 COOH (acetic acid) acids. Cu deposition under different acidic baths for different routes is presented and compared based on their electrical performance, scanning electron microscopy (SEM) and energy dispersive X-ray spectrometry (EDS). The result shows that chromic acid etched samples shows better electrical performance and Cu deposition in all acidic baths in comparison to sample etched via H2 SO4 /H2 O2 .